2009
DOI: 10.1159/000215942
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score to Predict the Outcome of Patients with Cerebral Vein and Dural Sinus Thrombosis

Abstract: Background: Around 15% of patients die or become dependent after cerebral vein and dural sinus thrombosis (CVT). Method: We used the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) sample (624 patients, with a median follow-up time of 478 days) to develop a Cox proportional hazards regression model to predict outcome, dichotomised by a modified Rankin Scale score >2. From the model hazard ratios, a risk score was derived and a cut-off point selected. The model and the score were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 13 publications
7
76
1
1
Order By: Relevance
“…Douglas et al reported that frequency of peripartum intracranial venous thrombosis is 8.9 to 11.6 cases per 100 000 deliveries (23,24) . In our cohort 33.33% of the females were in the postpartum state as opposed to 15% reported from the west (21,25) . The plausible reason for this difference include home deliveries in unhygienic environments and certain rites like water deprivation during immediate postpartum period.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Douglas et al reported that frequency of peripartum intracranial venous thrombosis is 8.9 to 11.6 cases per 100 000 deliveries (23,24) . In our cohort 33.33% of the females were in the postpartum state as opposed to 15% reported from the west (21,25) . The plausible reason for this difference include home deliveries in unhygienic environments and certain rites like water deprivation during immediate postpartum period.…”
Section: Discussioncontrasting
confidence: 56%
“…Clinical presentation of our cohort is almost identical to what has been reported from the west. 88.88% percent of our patients had mental status changes including drowsiness, confusion, and agitation, as compared to 22% reported in International Study on Cerebral Venous and Dural Sinus Thrombosis (ISCVT) (21,22) . We noted a median duration from symptom onset to hospital presentation as 5days, as compared to 4 days in other reports (21,22) .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…6,10,89 Table 6 summarizes demographic, imaging, and clinical variables associated with poor prognosis. 281,282 A Glasgow Coma Scale score of 14 to 15 on admission, a complete or partial intracranial hypertension syndrome (including isolated headache) as the only manifestation of CVT, and absence of aphasia were variables associated with a favorable outcome. 117,177 …”
Section: Risk Factors For Long-term Poor Outcomesmentioning
confidence: 98%
“…Sex was included in only 6% (1/16) of models predicting any outcome among patients with hemorrhagic stroke, as compared to 24% (6/25) of such models among ischemic stroke patients. Study‐ and model‐level characteristics of the 30 stroke‐related CPMs that included sex are presented in Table 2 25, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54…”
Section: Resultsmentioning
confidence: 99%